2020
DOI: 10.21203/rs.3.rs-34833/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between sexual violence and unintended pregnancy among adolescent girls and young women in South Africa

Abstract: Background Unintended pregnancy has dire consequences on the health and socioeconomic wellbeing of adolescent girls and young women (AGYW) (aged 15-24 years). While most studies tend to focus on lack of access to contraceptive information and services, and poverty as the main contributing factor to early-unintended pregnancies, the influence of sexual violence has received limited attention. Understanding the link between sexual violence and unintended pregnancy is critical towards developing a multifaceted in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Our ndings on how poverty, lack of contraceptives and sexual violence contribute to adolescent pregnancy are consistent with previous literature [11][12][13]. There is evidence that sexual violence and poverty are associated with higher probability of adolescent pregnancy.…”
Section: Discussion Of Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…Our ndings on how poverty, lack of contraceptives and sexual violence contribute to adolescent pregnancy are consistent with previous literature [11][12][13]. There is evidence that sexual violence and poverty are associated with higher probability of adolescent pregnancy.…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…For example, a mixed-methods study by Ajayi et al, [10] showed that higher proportions of unintended adolescent pregnancies in Kenya were among girls out-of school, married and not using contraceptives. Other studies identi ed early sex and marriage, wealth status, low contraceptive use, low educational levels, low socio-economic status, limited knowledge of sexual and reproductive health, and physical/sexual violence as drivers of adolescent pregnancy [11][12][13]. Interestingly, studies show that adolescent pregnancy and school dropout usually have the same drivers, including early sexual debut and poverty.…”
Section: Introductionmentioning
confidence: 99%
“…These have an overall negative impact on women's health [1,3,4]. Furthermore, sexual IPV increases the risk of an unplanned, mistimed, or unintended pregnancy among women, who lack access to family planning methods [5][6][7][8]. High-risk fertility behaviour is one hypothesized activity in which sexual IPV influences unwanted pregnancy and related health effects in mothers [9].…”
Section: Introductionmentioning
confidence: 99%
“…Existing models of care have failed to adequately address the gap in sexual health needs, access to- and uptake of-HIV and contraceptive services among adolescents in South Africa (1). The rate of unintended pregnancy among adolescents remains high, with about a quarter of adolescent girls and young women (AWYG) giving birth before age 20 (2)(3). According to UNAIDS, the incidence rate for HIV infection among adolescents aged 10-19 was 54 per 1000 population in 2018 in South Africa with adolescent girls disproportionally affected(4).…”
Section: Introductionmentioning
confidence: 99%